Biodiversity of macrofungi in Imphal, India-I - G.K.N. CHHETRY, M. NABAKANTA SINGH* (Indian Phytopathology, 2010)
This paper gives an account of fungal species belonging to six different genera of macrofungi. These fungi were obtained from twelve different plant substratum of Manipur forest. Out of these the species to genus Ascocoryne, Macrolepiota, Polyporus and Merulis are new report to India, while the species of Auricularia, and Schizophyllum are recorded on wide variety of substrate.